The size-weight illusion in visual form agnosic patient DF. Issue 5 (2nd September 2020) - Hassan, Eleanor K; Sedda, Anna; Buckingham, Gavin; McIntosh, Robert D
ABSTRACT: The size-weight illusion is a perceptual illusion where smaller objects are judged as heavier than equally weighted larger objects. A previous informal report suggests that visual form agnosic patient DF does not experience the size-weight illusion when vision is the only available cue to object size. We tested this experimentally, comparing the magnitudes of DF's visual, kinesthetic and visual-kinesthetic size-weight illusions to those of 28 similarly-aged controls. A modified t-test found that DF's visual size-weight illusion was significantly smaller than that of controls (zcc  = −1.7). A test of simple dissociation based on the Revised Standardized Difference Test found that the discrepancy between the magnitude of DF's visual and kinesthetic size-weight illusions was not significantly different from that of controls (zdcc  = −1.054), thereby failing to establish a dissociation between the visual and kinesthetic conditions. These results are consistent with previous suggestions that visual form agnosia, following ventral visual stream damage, is associated with an abnormally reduced size-weight illusion. The results, however, do not confirm that this reduction is specific to the use of visual size cues to predict object weight, rather than reflecting more general changes in the processing of object size cues or in the use of predictive strategies for lifting.